Partisipasi Orang Tua Dalam Pendidikan Anak Pada Sekolah Dasar Tanjung Selamat Dan Kuttab Al-Fatih (KAF) - Rahmah, Mawaddah; Martunis, Martunis; Khairiah, Khairiah (Jurnal Suloh, 2022)
The participation of parents in the implementation of children's education in schools is very important. This study aims to determine the description of parental participation in the implementation of children's education at Tanjung Selamat and Kuttab Al-Fatih Elementary Schools (KAF). This research was conducted at Tanjung Selamat and Kuttab Al-Fatih Elementary Schools (KAF) in Aceh Besar district. The subjects of this study were 1 teacher and 5 parents from each school. The approach used in this research is descriptive qualitative. Data collection techniques in the form of interviews and documentation. Based on the results of the study, it shows that the picture of parental participation in Tanjung Selamat Elementary School is still lacking where the form of participation carried out by parents is only in the form of participation in thoughts, energy and goods. Meanwhile, the participation of parents in Kuttab Al-Fatih (KAF) is in the form of thinking participation, special expertise, goods and money